PENATALAKSANAAN FISIOTERAPI PADA KASUS OSTEOARTHRITIS GENU BILATERAL DENGAN MENGGUNAKAN MODALITAS TENS, SWD DAN QUADRICEPS SETTING DI RSU PINDAD KOTA BANDUNG - Selvani Milenia; Ika Rahman (Journal of Health Science and Physiotherapy, 2021)
Osteoarthritis genu is a movable joint disease. This disease is a chronic progressive walking disease, which is characterized by inflammation of the articular cartilage and inflammation of the synovial membrane, which causes pain, stiffness in the joints, decreased muscle strength, and even decreased mobility.To find out the benefits of TENS, SWD and Quadriceps Setting in reducing pain, increasing muscle strength, knowing the Physiotherapy action plan, knowing the evaluation of Physiotherapy actions in patients with Bilateral Genu Osteoarthritis. After giving physiotherapy 6 times, the pain value decreased from T1: 3 to T6: 1, Movement from T1: 4 to T6: 2. Then Knee Dekstra Press from T1: 2 to T6: 1, Move from T1: 3 to T6: 1. Increase the strength of the left Flexor and Extensor muscles from T1: 4 to T6: 5. TENS, SWD, and Quadriceps Setting can help reduce pain and increase muscle strength in cases of Bilateral Genu Osteoarthritis